2016
DOI: 10.5812/ijem.38440
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Changes in Undercarboxylated Osteocalcin and Muscle Function in Hypoparathyroidism

Abstract: BackgroundMuscles and bones are interconnected. Recent studies suggest that undercarboxylated osteocalcin from bone may affect muscle mass and strength. There are, however, no prospective human data on this relationship.MethodsWe previously treated patients with hypoparathyroidism with intact Parathyroid Hormone (PTH) or placebo in a six-month randomized, placebo-controlled trial and demonstrated a marked increase in undercarboxylated osteocalcin (ucOC) in the PTH-treated group. We therefore investigated if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Our data identify ucOC as a potential therapeutic target for alleviating the reduction in muscle mass associated with muscle disorders and ageing. To the best of our knowledge, only a few human studies have investigated osteocalcin in relation to muscle mass and function, and these studies have led to inconsistent conclusions [48][49][50]; thus, the role of ucOC in muscle mass and physical function in humans is still unknown. Further research in humans is needed to confirm the data obtained inanimal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our data identify ucOC as a potential therapeutic target for alleviating the reduction in muscle mass associated with muscle disorders and ageing. To the best of our knowledge, only a few human studies have investigated osteocalcin in relation to muscle mass and function, and these studies have led to inconsistent conclusions [48][49][50]; thus, the role of ucOC in muscle mass and physical function in humans is still unknown. Further research in humans is needed to confirm the data obtained inanimal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Enhance C2C12 myoblast cell proliferation and myogenic differentiation thorough activation of the PI3K/Akt, p38 and GPRC6A-ERK1/2 signaling pathway separately . Positive associated with muscle mass or function (Levinger et al, 2014;Harslof et al, 2016;.…”
Section: The Effects Of Irisin On Osteoblastsmentioning
confidence: 99%
“…Later, Liu S. et al (2017) illustrated and confirmed that under-carboxylated OCN enhances C2C12 myoblast cell proliferation and myogenic differentiation thorough activation of the PI3K/Akt, p38, and GPRC6A-ERK1/2 signaling pathways, respectively. Moreover, several investigations on rats, healthy volunteers, or patients with hypoparathyroidism revealed that under-carboxylated OCN is positively associated with muscle mass or function ( Levinger et al, 2014 ; Harslof et al, 2016 ; Lin et al, 2016 ). However, this experiment should be repeated in a large healthy population.…”
Section: Proteome Altered With Age In Bone-muscle Crosstalkmentioning
confidence: 99%
“…In a cross-sectional study of women aged ≥70 years in which ucOC was assayed using a HAP-binding assay, a positive correlation was found between % ucOC and quadriceps muscle strength [ 120 ]. In an interventional study of 62 patients with hypoparathyroidism, treatment with recombinant parathyroid hormone (rPTH) resulted in an increase in % ucOC which was not associated with energy metabolism [ 121 ], but was positively associated with the change of maximum force generated in elbow extension [ 122 ]. However, in that study, the increase in ucOC was not associated with other tests of muscle and physical performance [ 122 ].…”
Section: Osteocalcin Exercise and Muscle Function—experimental Stmentioning
confidence: 99%
“…In an interventional study of 62 patients with hypoparathyroidism, treatment with recombinant parathyroid hormone (rPTH) resulted in an increase in % ucOC which was not associated with energy metabolism [ 121 ], but was positively associated with the change of maximum force generated in elbow extension [ 122 ]. However, in that study, the increase in ucOC was not associated with other tests of muscle and physical performance [ 122 ]. Therefore, while there is some data to support a role for ucOC in the regulation of muscle strength and function, in addition to its role in muscle glucose uptake and metabolism, interventional studies are needed to determine if there is a causative effect and whether there is scope for novel therapeutic approaches to enhance both glucose metabolism and muscle function.…”
Section: Osteocalcin Exercise and Muscle Function—experimental Stmentioning
confidence: 99%